Nexus Between Monetary Policy And Food Inflation In South Asian Countries: An Empirical Review - Ali, Choudary Ihtasham; Raza, Mohsin; Tahir, Maryam; Arshad, Nabiha; Tanveer, Minahil; Ejaz, Iqra; Faiz, Najeeb (South Asian Journal of Social Sciences and Humanities, 2025)
Purpose of the Study: This review is carried out to investigate the nexus between monetary policy and food inflation in South Asia. Methodology: The review synthesizes the findings of empirical studies, describing that there is a need to adopt an integrated approach to implement monetary policy with structural reforms, to reduce market inefficiencies, and to enhance agricultural productivity for long-term food price stability. Findings: It is highlighted in the literature that structural inefficiencies, supply-side restraints, and vulnerability to external shocks result in food price volatility in the countries of the region. Traditionally, monetary policy measures are employed to tackle overall inflation in countries, but their effectiveness in addressing food inflation is insufficient due to dominant structural inefficiencies. The review also points out the effects of food inflation on the welfare of vulnerable populations. Application of the Study: It is recommended that targeted food security programs with fiscal measures be employed to improve the welfare of affected populations. Originality of the Study: This study comprehensively reviews the relationship between monetary policy and food inflation in South Asia, highlighting the unique structural inefficiencies and supply-side constraints that differentiate food inflation from general inflation. It emphasizes the need for an integrated policy approach, contributing to the existing literature by offering a region-specific perspective on food price stability and welfare implications.
Keywords: Food Inflation; Monetary Policy; South Asia; Macroeconomic Factors